481 Association of liver abscess presence and severity with trim loss, harvest yield, carcass grading performance, lung lesions, and value of fed Holsteins. (7th December 2018) - Herrick, R; Rogers, C; Jones, T; McEvers, T; Brown, T; Maxwell, C; Lawrence, T
Abstract: Fed Holsteins were tracked through two commercial processing facilities, one in the High Plains ( n =1, 073) and one in the Central Plains ( n =1, 070). Our objective was to evaluate the effect of liver abscesses on carcass characteristics and value of calf-fed Holstein carcasses. Liver abscesses were visually assessed, while simultaneously, lungs were palpated to assess degree of consolidation and fibrin tag formation. Carcass trim was weighed from carcasses moved off-line for zero tolerance trimming. Carcass and viscera values were assigned using USDA market reports and adjusted based on viscera condemnations, and premiums and discounts for quality and yield outcomes. Data were analyzed using the MIXED and GENMOD procedures of SAS v9.4 (SAS Inst. Inc., Cary, NC) with carcass as the experimental unit. Cattle exhibited liver abnormality rates of A- (3.73%), A (7.28%), A+ (7.56%), A+Adhesion (A+AD; 17.50%), A+Open (A+OP; 4.39%), A+Adhesion/Open (A+AD/OP; 3.92%), and Contamination (6.16%), with 49.46% of livers being edible. Hot carcass weight was reduced ( P < 0.05; -25.1 kg, -6.6%) in carcasses that had an A+AD/OP liver abscess when compared to carcasses with edible livers. Carcasses with A+AD/OP or A+OP liver scores had increased ( P < 0.01) carcass trim (3.39 and 3.92 kg, respectively), when compared to carcasses with edible livers (0.38 kg). A greater degree ( P P=0.03; -110.99/carcass) by 7.3% for carcasses with A+AD/OP liver outcomes when compared to carcasses with edible livers. Although not different ( P =0.27), carcasses with A+AD and A+OP liver outcomes were worth 4.9 and 4.6% less, respectively (-73.93 and -69.65/carcass, respectively) than carcasses with edible livers. Unless the liver abscess issue is addressed by the fed beef industry, Holsteins will continue to incur great financial risk to the beef industry.